2020
DOI: 10.1016/j.molcel.2020.02.028
|View full text |Cite
|
Sign up to set email alerts
|

ATF7-Dependent Epigenetic Changes Are Required for the Intergenerational Effect of a Paternal Low-Protein Diet

Abstract: Highlights d ATF7 is required for paternal diet-induced expression changes in mouse offspring d ATF7 binds to the promoter regions and induces H3K9me2 in testicular germ cells d Low protein diet causes ATF7 activation and H3K9me2 reduction via ROS production d ATF7 regulates epigenetic status and small RNA expression profile in spermatozoa

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 68 publications
1
56
0
Order By: Relevance
“…In fact, some authors described that the expression of some sperm small RNAs and tsRNAs rapidly changed in relation to male high-sugar diets [75,76]. The profiles of these RNA were related to sperm quality and embryo viability [77], and may also affect histone modifications and tsRNA biogenesis at the testis level [78]. Therefore, epigenetic components are important affectations to be studied when sperm cells are subjected to an oxidative environment.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, some authors described that the expression of some sperm small RNAs and tsRNAs rapidly changed in relation to male high-sugar diets [75,76]. The profiles of these RNA were related to sperm quality and embryo viability [77], and may also affect histone modifications and tsRNA biogenesis at the testis level [78]. Therefore, epigenetic components are important affectations to be studied when sperm cells are subjected to an oxidative environment.…”
Section: Discussionmentioning
confidence: 99%
“…These challenging situations in tsRNA research await clarification and resolution. [63,64], epigenetic inheritance [42,[65][66][67][68], and symbiosis [69]. Unlike other canonical sncRNAs such as miRNAs, siRNAs, and piRNAs, which usually function through strict molecular mechanisms by binding to Argonaute family proteins, the mechanisms of action of tsRNAs appear to be more diverse.…”
Section: Evolving Tsrna Functionalitiesmentioning
confidence: 99%
“…Recently, we found that the transcription factor ATF7 is a key factor for intergenerational inheritance of traits resulting from pLPD in mice (Yoshida et al, 2020). In testicular germ cells (TGCs), ATF7 binds to promoter regions and induces methylation of histone H3 lysine 9 (H3K9me2) via physical interaction with the…”
Section: Introductionmentioning
confidence: 99%